Treatment of Chronic Acne by Persian Medicine (Temperament Modification plus Leech Therapy): A Case Report - Hoorieh Mohammadi Kenari; Gholamreza Kordafshari; Maryam Moghimi (Tehran University of Medical Sciences, 2020)
Acne is a multifactorial disease which causes many harmful physical and psychological effects for patients. Several therapies are used in conventional medicine for acne, but most of these methods are not stable and cause side effects. Therefore, it is considered to use complementary medicine alongside conventional therapies to achieve better results. In this article, a patient with chronic and severe acne is presented which is treated by a combination of temperament modification and leech therapy based on Persian medicine.